ARTIFICIAL INTELLIGENCE AS A SUPPORT TOOL IN TEACHING PROGRAMMING TO FUTURE BACHELOR'S STUDENTS OF VOCATIONAL EDUCATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article presents a thorough examination of the potential applications of artificial intelligence (AI) in supporting the instruction of programming to future bachelor's degree students in vocational education. It explores the pivotal domains of AI integration into the educational process, encompassing the utilization of adaptive learning systems, intelligent tutoring systems, automated code evaluation systems, and generative models that enhance both the theoretical and practical training of students. It demonstrates the ways in which AI enhances the personalization of educational content, facilitates rapid feedback loops, and optimizes the verification process of software solutions. It has been determined that the integration of AI facilitates the creation of adaptive learning environments. In such environments, automated algorithms analyze test results, the history of students' interaction with educational materials, and the personal pace of information assimilation. Consequently, this facilitates the development of customized educational pathways that are tailored to the distinct characteristics of each student. The implementation of intelligent tutoring systems, such as ChatGPT, GitHub Copilot, or Google AI Studio based on Gemini, facilitates the elucidation of complex programming concepts, including the principles of recursion, sorting algorithms, and other fundamental principles. This, in turn, contributes to the cultivation of critical thinking and self-study skills. In the article, the authors analyze the challenges associated with the introduction of AI in the educational process. The primary challenges identified pertain to issues of academic integrity, particularly when future bachelors of vocational education employ AI capabilities to automatically generate solutions without a comprehensive grasp of the subject matter. Additionally, the article addresses technical limitations concerning the substantial computing resources required and the integration of contemporary algorithms into existing educational platforms. The article further underscores the necessity for specialized professional development programs to equip educators with the skills to effectively utilize AI in vocational education. Additionally, it emphasizes the establishment of ethical frameworks to guide the implementation of AI technologies in this context, ensuring that the principles of academic integrity are preserved and the integrity of the educational process is maintained. The authors of the article propose a number of recommendations and approaches to optimize the process of AI integration, create integrated learning environments, and improve existing assessment methods with regard to automated code verification. The findings of the study can be utilized to enhance pedagogical approaches in programming, to improve the quality of training in the field of information technology, and to promote the development of competitive graduates.